Silkworm Pupae Meal: A Potential Unconventional Protein Source for Animal Feeding - Sahib, Qazi Shehriyar; Ahmed, Haidar Ali; Beigh, Yasir Afzal; Syed Mohmad Shah; Ganai, Abdul Majeed; Javid Farooq; Sheikh, Gowher Gull (Indian Journal of Animal Nutrition, 2024)
ABSTRACT:Silkworm pupae are thrown away as a waste by-product of silk industry after reeling silk from the cocoons. The huge amount of the pupae produced/disposed (about 5500 pupae per kg of raw silk), pose a severe pollution threat to environment, soil and water. This demands technological interventions for efficient disposal or utilization of these pupae in a productive enterprise. Considering the fact that the pupae represent an active growth stage of an insect, they offer a potential nutrient-rich alternative for livestock feeding. Off-late, the silkworm pupae meal (SWPM) has been acknowledged as top-class protein source of animal origin that finds way in utilization as a low-cost unconventional feeding resource for livestock and poultry. It has a high nutritive value and acts as a decent source of protein, carbohydrates, fat, fiber, ash, methionine, lysine, calcium and phosphorus, and could offer a cheap animal food for the growing livestock sector which is generally regarded as resource-hungry in terms of insufficient availability of quality feed and fodder. The increasing dependence of expanding mankind on animal proteins, in decreasing availability of plant-based proteins, further necessitates the development of strategies and policies for harnessing the industrial by-products as alternate animal-foods and SWP finds its best use as an alternate, economical and efficient animal food.